PENERAPAN E-TILANG BAGI PELANGGAR LALU LINTAS DI WILAYAH HUKUM POLDA BALI - Mertha, I Putu Suda (Kerta Dyatmika, 2024)
The implementation of Electronic Traffic Law Enforcement (E-Tilang) represents an initiative by the police to enhance the quality of public services by making them more effective, efficient, transparent, and accountable. Within the jurisdiction of the Bali Regional Police (Polda Bali), the E-Tilang system is applied to traffic and road transport violators by the Law Enforcement Sub-Directorate (Subdit Gakkum), based on Law Number 22 of 2009 concerning Road Traffic and Transportation, and Government Regulation Number 80 of 2012 concerning Procedures for Motor Vehicle Inspection on the Road and the Handling of Traffic and Road Transport Violations. This study aims to examine the implementation of the E-Tilang system within the jurisdiction of Polda Bali and to identify the challenges encountered during its application. The research employs an empirical legal research method. Data were obtained through field observation and analyzed qualitatively to provide a comprehensive understanding of the effectiveness of E-Tilang implementation. The research findings indicate that the E-Tilang system or ETLE (Electronic Traffic Law Enforcement) functions as an electronic recording tool for traffic violations. Offenders receive a notification letter requesting confirmation of the recorded violation. However, several challenges were identified, including inconsistencies in vehicle ownership data where the registered owner differs from the actual violator due to unupdated documentation, and limited ETLE infrastructure coverage on certain road segments. The study concludes that although E-Tilang has improved the efficiency of traffic law enforcement, technical and administrative obstacles remain. Solutions implemented include requiring previous vehicle owners to coordinate with ETLE officers by providing evidence of sale and purchase, as well as the use of Mobile ETLE an enforcement system installed in police vehicles or operated via mobile devices to allow more flexible and widespread monitoring of traffic violations.